2012
DOI: 10.1257/aer.102.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Privacy Concerns

Abstract: This paper explores how digitization and the associated use of customer data have affected the evolution of consumer privacy concerns. We measure privacy concerns by reluctance to disclose income in an online marketing research survey. Using over three million responses over eight years, our data show: (1) Refusals to reveal information have risen over time, (2) Older people are less likely to reveal information, and (3) The difference between older and younger people has increased over time. Further analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(60 citation statements)
references
References 18 publications
1
42
0
Order By: Relevance
“…In fact, the observation that people seem not to protect their privacy online very aggressively does not justify the conclusion that they never do so. Tsai et al (2011) find that consumers are, sometimes, willing to pay a price premium to purchase goods from more privacy-protective merchants; Goldfarb and Tucker (2012b) use surveys to measure respondents' implied concern for privacy by their willingness to disclose information about income, and find evidence of privacy concerns increasing over an eight-year period; Stutzman, Gross, and Acquisti (2012) find evidence of increasing privacy-seeking behavior among a sample of over 4,000 early Facebook members; Kang, Brown, and Kiesler (2013) document Internet users' attempts to maintain anonymity online; and Boyd and Marwick (2011) discuss various alternative strategies teenagers adopt to protect their privacy while engaging in online sharing.…”
Section: Consumer Attitudes and Behaviorsmentioning
confidence: 99%
“…In fact, the observation that people seem not to protect their privacy online very aggressively does not justify the conclusion that they never do so. Tsai et al (2011) find that consumers are, sometimes, willing to pay a price premium to purchase goods from more privacy-protective merchants; Goldfarb and Tucker (2012b) use surveys to measure respondents' implied concern for privacy by their willingness to disclose information about income, and find evidence of privacy concerns increasing over an eight-year period; Stutzman, Gross, and Acquisti (2012) find evidence of increasing privacy-seeking behavior among a sample of over 4,000 early Facebook members; Kang, Brown, and Kiesler (2013) document Internet users' attempts to maintain anonymity online; and Boyd and Marwick (2011) discuss various alternative strategies teenagers adopt to protect their privacy while engaging in online sharing.…”
Section: Consumer Attitudes and Behaviorsmentioning
confidence: 99%
“…A large number of studies in recent years support this logic. Scholars have noted the growing prevalence of privacy concerns amongst consumers (Goldfarb and Tucker 2012), and have demonstrated the positive effects of privacy assurances, policies and seals on user information sharing and product purchase (Hui et al 2007;Tsai et al 2011). At the same time, a number of studies have demonstrated the value of social recognition and reputational gains as drivers of user contributions to online communities (Wasko and Faraj 2005;Zhang and Zhu 2011).…”
Section: Introductionmentioning
confidence: 99%
“…First, it is important to acknowledge that privacy concerns about targeted advertisements depend on situational factors, including the product being promoted in the message (e.g., Acquisti, Brandimarte, & Loewenstein, 2015;Goldfarb & Tucker, 2012). Thus, the findings in the present study might have been influenced by our choice to use a test ad promoting a pair of shoes.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 91%